PENGARUH INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE MELALUI INNOVATION CAPABILITY SEBAGAI INTERVENING VARIABLE PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - Essianda, Ivana (Business Accounting Review, 2016)
This study was conducted to know whether the positive effect on the Intellectual Capital on Innovative Capability, Innovative Capability on Financial Performance, and Intellectual Capital on Financial Performance in Public Accounting Firm in Surabaya. This study used a quantitative approach, and the data were obtained through distributing questionnaires to public accounting firms in Surabaya and processed by using smartPLS software. This study showed that there was a positive and significant relationship of intellectual capital to innovation capability; innovation capability to financial performance; and intellectual capital to financial performance in public accounting firm in Surabaya. But, innovation capability was inadequate to be an intervening variable between intellectual capital and financial performance because the direct relationship between intellectual capital and financial performance gave greater affect than if it was through innovation capability.